Respuesta :
For this case we have a function of the form [tex]y = g (x)[/tex]
Where:
[tex]g (x) = x ^ 2 + 2[/tex]
We must find the value of the function when x = 3. Then we substitute:
[tex]g (3) = 3 ^ 2 + 2\\g (3) = 9 + 2\\g (3) = 11[/tex]
Thus, the value of the function when [tex]x = 3[/tex] is [tex]y = 11[/tex]
Answer:
[tex]g (3) = 11[/tex]
Option C
Answer: Third Option
[tex]g(3) = 11[/tex]
Step-by-step explanation:
We have the function [tex]g(x) = x^2 + 2[/tex] and we must find the value of g(3).
To find g (3) we must evaluate the function g(x) for x = 3. That is, we must replace x = 3 in the function
Then
[tex]g(x) = x^2 + 2[/tex]
[tex]g(3) = (3)^2 + 2[/tex]
[tex]g(3) = 9 + 2[/tex]
[tex]g(3) = 11[/tex]
Finally the correct answer is the third option